Functional Traits Explain Variation in Chaparral Shrub Sensitivity to Altered Water and Nutrient Availability - Nielsen, Reina L.; James, Jeremy J.; Drenovsky, Rebecca E. (Frontiers in Plant Science, 2019)
Worldwide, drylands are threatened by changes in resource availability associated with global environmental change. Functional traits may help predict which species will be most responsive to these alterations in nutrient and water availability. Current functional trait work focuses on tissue construction and nutrient concentrations, but plant performance in low resource environments also may be strongly influenced by traits related to nutrient budgets and allocation. Our overall objective was to compare trait responses in a suite of serpentine and non-serpentine congener pairs from the California chaparral, a biodiverse region facing nutrient deposition and future changes in precipitation. In a common garden greenhouse environment, we grew small plants of Arctostaphylos manzanita, A. viscida, Ceanothus cuneatus, C. jepsonii, Quercus berberidifolia, and Q. durata in contrasting soil nutrient and moisture treatments. We measured a suite of traits representing physiological, growth, and mineral nutrient responses to these treatments. Overall, plant growth rate and leaf-level phosphorus use efficiency were greatest in the low water, high nutrient treatment and lowest in the high water, low nutrient treatment. Variation in growth rate and plasticity among species and treatments was primarily associated with differences in mineral nutrition-based traits as opposed to differences in biomass allocation or specific leaf area. Namely, faster growing species and species with greater plasticity allocated more nitrogen and phosphorous to leaves and demonstrated greater photosynthetic phosphorus use efficiency. Overall, non-serpentine species had greater plasticity and biomass response to resource addition than serpentine species, and congener pairs responded to these resource additions more similarly to each other than species across congener pairs. This study extends our general understanding of how functional traits may influence species responses to environmental change and highlights the need to integrate mineral nutrition-based traits, including allocation of nutrient pools and nutrient use efficiency, into this larger trait framework. Ultimately, this insight can help identify, in part, why coexisting species may vary in sensitivity to anthropogenic driven changes in soil resource availability.